Archaeological Research in the Laguna de Bay area, Philippines - Vitales, Timothy James (Hukay; Vol 18, 2013)
This paper outlines the archaeological undertakings conducted around the Laguna de Bay one of the most prominent lake features in southern Luzon, Philippines. Since the beginnings of the discipline and its research in this archipelago, the Laguna de Bay area has demonstrated its rich archaeology from the sites discovered and artefacts recovered dating from the Palaeolithic to the historic period. However, despite the abundance of archaeological data gathered from this significant region, our knowledge on the prehistory of Laguna de Bay area somehow still needs to be fully explored and understood. Realising its archaeological potential, an extensive multi-disciplinary research focusing on the whole lakeshore is crucial in our understanding of the role of Laguna de Bay in the archaeology of the region; from the development of communities around it to the environmental and cultural-historical processes that might have occurred and affected the area.